Monipaikkainen kansallisuus - Prokkola, Eeva-Kaisa (Terra, 2011)
Bordering : identity processes between the national and personal / Anders Linde-Laursen. Burlington : Ashgate, 2010.
Keywords: Linde-Laursen, Anders; raja-alueet - Ruotsi - Tanska; kansallisuus2 ysa